Exploring the diffusion of low energy houses: An empirical study in the European Union - Mark Olsthoorn; Joachim Schleich; Corinne Faure (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
Diffusion of low-energy houses is an important part of energy and climate policy in the European Union (EU) and in individual EU countries. Key barriers to the adoption of low-energy houses include additional construction costs and uncertainty surrounding actual energy and cost savings. In this paper, we econometrically analyze determinants of low-energy house adoption, including time and risk preferences. We rely on original data from a large survey conducted among households in eight EU countries. To our knowledge, this is the first empirical study of low-energy building adoption to rely on a demographically representative sample. Our set of covariates includes parameters of time and risk preferences that were elicited via state-of-the-art incen-tivized multiple price list experiments and via self-assessment scales. We find mixed results for the effects of time discounting on low-energy house adoption. Risk preferences do appear to matter: as risk proneness increases, so does the adoption of zero net or energy plus building (but not passive houses). Consistent with the low-cost hypothesis about environmental attitude and action, we find no results for environmental attitudes and social norms.
urn:nbn:de:0011-n-5033509
Keywords: 330; passive houses; low-energy houses; adoption; buildings; risk; patience